Residue of the process red propolis extract in commercial ration on performance of Nile tilapia fingerlings (Oreochromis niloticus) - Santos, Elton Lima; da Silva, Fabio Cristiano Belarmino; Pontes, Edvânia da Conceição; Lira, Rosa Cavalcante; Cavalcanti, Maria Caroline Almeida (Comunicata Scientiae, 2013)
The aim was to evaluate the addition of different levels the residue of the alcoholic extract of red propolis as an additive in diets for Nile tilapia fingerlings. We used 80 fingerlings of tilapia (Oreochromis niloticus) masculinized with initial weight of 0.11 ± 0.03 g, distributed in 20 aquariums of 15L of water in a completely randomized design with four treatments and five replications in a recirculation system water with constant aeration. The diets were prepared with commercial ration mashed with the addition of (0, 0.50, 1.00 and 1.50%) of residue. The variables studied were: ultimate weight (UW), Weight gain (WG), Whole-length (WL), Standard length (SL), Length of head (LH), Index profile (IP), Index head (IH), Condition factor (CF), Width and Height. There was no positive effect (P<0.05) of the use of red propolis residue on the productive performance of animals.